The instructional and learning quality: The effect of four teacher competencies - Taufiq Satria Mukti; Kartika Satya Noviafitri (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2024)
Teacher competence is directly proportional to  student learning quality. The purpose of this study was to prove whether teacher competence positively impacts the quality of learning. The study was conducted on 127 state madrasah teachers in Malang Regency and Batu City. Data was collected using a questionnaire via Google Form with a semantic differential scale (1-10). The instrument was developed in accordance with the teacher competence law and has met the quality requirements of content testing by experts and obtained empirical evidence in the SEM analysis with CFI (Comparative Fit Index) results, 0.926, RMSEA 0.110, CI (Confidence interval) 0.0937-0.126, and Reliability 0,95. The test of the influence of teacher competence on the quality of learning was carried out using linear regression analysis. The results of the data analysis obtained in the study showed a positive influence of teacher competence on the quality of learning by 90.8%. The results of measurements with the instrument used by the researcher can be a reference in measuring teacher competence;; the better the teacher's competence is, the more directly proportional it is to the quality of learning.